Recurrent pseudogout after therapy with immune checkpoint inhibitors: a case report with immunoprofiling of synovial fluid at each flare. Issue 1 (14th May 2019) - Kim, Sang T.; Bittar, Mohamad; Kim, Hyun J.; Neelapu, Sattva S.; Zurita, Amado J.; Nurieva, Roza; Suarez-Almazor, Maria E.
Abstract : Background: Despite ground-breaking clinical success in the treatment of different cancers, immune checkpoint inhibitors can cause profound inflammatory and immune-related adverse events. Autoimmune inflammatory arthritis following immune checkpoint inhibitor treatment has been reported; however, to date, no cases of crystal arthritis following immune checkpoint inhibitors have been identified. Case presentation: We report the first case of recurrent pseudogout, an inflammatory crystal arthritis, in a patient treated with nivolumab, a PD-1 inhibitor, for renal cell carcinoma. The patient had recurrent pseudogout flares about week to 10 days after each nivolumab infusion. After treatment with prophylactic colchicine, the patient well tolerated additional nivolumab infusions without adverse events. In parallel, we characterized immune cells of synovial fluid at each flare. Immunoprofiling of synovial fluid showed that the proportion of inflammatory IL-17-producing CD4 + T cells and amount of IL-17 were notably increased in synovial fluid with every recurrent flair, and correlated with the increase in number of synovial neutrophils, suggesting a potential role of T helper 17 (Th17) cells in neutrophil-driven inflammation during pseudogout arthritis. Conclusions: This case suggests a potential influence of Th17 cells on the neutrophil recruitment and neutrophil-driven inflammatory events leading to pseudogout induced by immune checkpoint inhibitor therapy.